2016
DOI: 10.2147/copd.s107326
|View full text |Cite
|
Sign up to set email alerts
|

Mid-arm and calf circumferences are stronger mortality predictors than body mass index for patients with chronic obstructive pulmonary disease

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is currently the third most common cause of death in the world. Patients with COPD experience airflow obstruction, weight loss, skeletal muscle dysfunction, and comorbidities. Anthropometric indicators are risk factors for mortality in geriatric assessment.PurposeThis study examined and compared the associations of anthropometric indicators, such as low body mass index (BMI), low mid-arm circumference (MAC), and low calf circumference (CC), with the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“… 37 , 38 Muscle atrophy appears as a major cause of decreased skeletal muscle strength, 39 while the circumference of the upper and lower limbs can strongly predict COPD mortality compared to BMI. 40 Similarly, skeletal muscle dysfunction as an independent risk factor can predict mortality in patients with COPD, 41 and it is closely related to reduced physical activity, exercise capacity, and quality of life. 42 Therefore, skeletal muscle function is an important component of the comprehensive condition of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 38 Muscle atrophy appears as a major cause of decreased skeletal muscle strength, 39 while the circumference of the upper and lower limbs can strongly predict COPD mortality compared to BMI. 40 Similarly, skeletal muscle dysfunction as an independent risk factor can predict mortality in patients with COPD, 41 and it is closely related to reduced physical activity, exercise capacity, and quality of life. 42 Therefore, skeletal muscle function is an important component of the comprehensive condition of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CC was found to be a reflector of health, performance, nutritional status, and survival ( 58 ). Shu-Chuan Hoet al also suggested CC as an accurate predictor of long-term risk of mortality in COPD ( 59 ). Consistently, other studies performed among elderly individuals have identified CC as an indicator of skeletal muscle mass, which could be used for diagnosing sarcopenia ( 58 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GOLD stage IV was associated with nine times increased risk of low MAMC in the present study. MAMC is an indicator of muscle mass and has an important role in COPD; its association with mortality in patients suffering from COPD is stronger than BMI ( Soler-Cataluña et al, 2005 ; Ho et al, 2016 ; Marquis et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%